Literature Review on The Impact of Monetary Policy on Economic Growth And Inflation - Roby Prasetyo; Syamsul Arifin; Devangga Putra Adhitya Pratama (CV Pena Jaya Pers, 2025)
This literature review synthesizes recent empirical and theoretical research examining the multifaceted relationship between monetary policy, economic growth, and inflation, with particular emphasis on emerging market economies, notably Indonesia. Drawing from 15 peer-reviewed articles indexed in Scopus and SINTA databases published between 2019 and 2024, this review elucidates the theoretical foundations and practical mechanisms through which central banks influence macroeconomic outcomes. The analysis reveals that monetary policy operates through multiple transmission channels, including interest rate adjustments, credit expansion, asset price effects, and exchange rate movements. The evidence demonstrates that moderate inflation accommodates economic growth through reduced real borrowing costs and investment incentives; however, inflation exceeding critical thresholdsidentified empirically at approximately 5-9.5 percent for Indonesiagenerates substantial economic costs through uncertainty and reduced purchasing power. The research underscores the essential role of fiscal-monetary policy coordination in achieving dual stability and growth objectives. Furthermore, findings indicate that monetary policy effectiveness varies substantially based on financial system development, inflation expectations anchoring, and global spillover effects. The review identifies that during crisis periods, including the COVID-19 pandemic, monetary policy transmission weakens considerably despite accommodative stances. Contemporary evidence supports data-dependent, forward-looking monetary policy frameworks combined with transparent communication regarding inflation targets. The synthesis concludes that optimal monetary policymaking in emerging markets requires integrated approaches incorporating macroprudential measures, credible inflation targeting regimes, and coordinated fiscal-monetary responses to structural shocks.